Review of Mediterranean members of the Aphaenogaster cecconii group (Hymenoptera: Formicidae), with description of four new species - Borowiec, Lech; Salata, Sebastian (Zootaxa, 2014)
A group of six Mediterranean species related to Aphaenogaster cecconii Emery is reviewed. Four new species are described: A. equestris (SW Turkey), A. jolantae (Greece, Rhodes), A. lykiaensis (SW Turkey) and A. olympica (Greece, Karpathos). Aphaenogaster cecconii Emery and A. phillipsi Wheeler & Mann are redescribed. Detailed measurements and some observations on the location of nests and activity of workers are given.